DEBT FINANCING AND PERFORMANCE OF MANUFACTURING COMPANIES IN NIGERIA - E. O., Efemena; C.I., Augustine (International Journal of Scientific Research and Management (IJSRM), 2024)
Certain companies have accumulated substantial debt that surpasses their net gains, which has a negative impact on their performance and investor trust. Consequently, this can ultimately end in complete collapse and even lead to closures. Based on the above corporate challenges this study examines into the effect of debt financing on performance of manufacturing companies in Nigeria. The study employed the descriptive survey design. The secondary panel data was sourced audited financial statement of selected manufacturing firms in Nigeria from the period of 2019-2022. The panel regression technique was employed to determine the relationship and magnitude of impact between the dependent variables and independent variables. The Hausman test was employed in taking decision from the pooled effect, fixed effect and random effect model.  The findings from objective one revealed that short term debt has negative significant effect on return on equity at (β:-0.23: p